The Nature and Predictive Power of Preferences: Global Evidence - Armin Falk; Anke Becker; Thomas Dohmen; Benjamin Enke; David B. Huffman; Uwe Sunde (Institute for the Study of Labor (IZA), 2015)
This paper presents the Global Preference Survey, a globally representative dataset on risk and time preferences, positive and negative reciprocity, altruism, and trust. We collected these preference data as well as a rich set of covariates for 80,000 individuals, drawn as representative samples from 76 countries around the world, representing 90 percent of both the world's population and global income. The global distribution of preferences exhibits substantial variation across countries, which is partly systematic: certain preferences appear in combination, and follow distinct economic, institutional, and geographic patterns. The heterogeneity in preferences across individuals is even more pronounced and varies systematically with age, gender, and cognitive ability. Around the world, our preference measures are predictive of a wide range of individual-level behaviors including savings and schooling decisions, labor market and health choices, prosocial behaviors, and family structure. We also shed light on the cultural origins of preference variation around the globe using data on language structure.
Keywords: D01; D03; F00; 330; economic preferences; cultural variation